UJI CEMARAN Escherichia coli PADA JAMU GENDONG DENGAN METODE MOST PROBABLE NUMBER - Hendiana, Siti Nurazizah Aghisna; Kasasiah, Ahsanal; Utami, Marsah Rahmawati (Jurnal Sains dan Teknologi Pangan, 2022)
ABSTRACTThe traditional herbal drink is a herbal medicine business that everyone can do because the processing is still effortless, and raw materials are easily obtained. The processing of traditional herbal drinks, which is still very simple, has limitations such as inadequate sanitation and hygiene, resulting in contaminated herbs and can endanger consumers' health. This study aims to identify contamination of Escherichia coli on traditional herbal drink, which is sold in 3 different locations in the East Karawang subdistrict. The samples of traditional herbal drinks were duplicated, consisting of beras kencur and kunyit asam with 12 samples. The sampling locations are Kondang Jaya, Adiarsa Timur, and Plawad areas. This contamination test uses the Most Probable Number method as a preliminary test for Escherichia coli contamination. Based on the results of the study, the MPN value data for the presumption test using Lactose Broth (LB) media and confirmation using Escherichia coli Broth (ECB) media ranged from 3-2400 MPN/mL. 2 out of 3 sellers of traditional herbal drink in the East Karawang subdistrict do not meet the requirements for the permitted contamination limit contained in the traditional herbal drink. The Eosin Methylene Blue Agar (EMBA) selective media test showed that all samples were positively contaminated with Escherichia coli. Contamination in traditional herbal drinks can be caused by the manufacturing process that does not pay attention to sanitation and hygiene, as well as contamination from other external factors.Keywords: Traditional herbal drink, Most Probable Number, Escherichia coliABSTRAK. Jamu gendong merupakan usaha jamu yang masih sangat sederhana proses pengolahannya serta bahan baku yang mudah didapatkan. Pengolahan jamu yang masih sangat sederhana ini memiliki keterbatasan seperti sanitasi dan higiene yang tidak memadai, sehingga mengakibatkan jamu terkontaminasi dan dapat membahayakan kesehatan konsumen. Penelitian ini bertujuan untuk mengidentifikasi cemaran bakteri Escherichia coli pada jamu gendong yang dijual di 3 lokasi berbeda di Kecamatan Karawang Timur. Sampel jamu gendong diambil secara duplo yang terdiri dari jamu beras kencur dan kunyit asam dengan jumlah total 12 sampel. Adapun lokasi pengambilan sampel yaitu daerah Kondang Jaya, Adiarsa Timur, dan Plawad. Uji cemaran ini menggunakan metode Most Probable Number sebagai uji pendahuluan cemaran Escherichia coli. Berdasarkan hasil penelitian, didapatkan data nilai MPN untuk uji praduga menggunakan media Lactose Broth (LB) dan penegas menggunakan media Escherichia coli Broth (ECB) berkisar 3-2400 MPN/mL, 2 dari 3 penjual jamu gendong di Kecamatan Karawang Timur tidak memenuhi persyaratan batas cemaran yang diizinkan terdapat dalam jamu. Hasil uji pada medium selektif Eosin Methylene Blue Agar (EMBA) didapatkan semua sampel positif tercemar Escherichia coli. Cemaran pada jamu dapat diakibatkan oleh proses pembuatan yang kurang memperhatikan sanitasi dan higiene, serta kontaminasi yang berasal dari faktor luar lainnya.Kata kunci: Jamu gendong, Most Probable Number, Escherichia coli